ATTITUDES TOWARD LESBIANS AND GAY MEN: RELATIONS WITH GENDER, RACE AND RELIGION AMONG UNIVERSITY STUDENTS - Arndt, Marlene; de Bruin, Gideon (PINS-Psychology in Society, 2025)
This study posits that although the South African government has shown an unprecedented commitment to acknowledging and upholding the human rights of lesbians and gay men, negative attitudes exist towards lesbians and gay men in university communities. A survey of 880 heterosexual students (356 men and 524 women) in a university community was conducted using the Attitudes Towards Lesbian and Gay Male Scale (ATLG). The results indicate that heterosexual students at a university in Gauteng have negative attitudes towards lesbians and gay men, that gender and religiosity has an influence on attitudes towards lesbians and gay men, and that no differences exist between race groups concerning attitudes towards lesbians and gay men. The results are discussed against the background of previous studies, and suggestions for future research are made.